An Unusual Foreign Body in the Airway of 11- Month-Old Girl Mimicking Bronchiolitis (Dhaka Shishu (Children) Hospital Journal, 2026)
Airway foreign body aspiration (FBA) remains one of the most common respiratory emergencies in early childhood, accounting for a major proportion of preventable deaths in children. But variable clinical and radiological features lead the diagnostic and therapeutic challenges. Here we report an 11-month-old previously healthy girl who developed sudden cough and respiratory distress without fever. She was wheezy but not toxic; chest radiograph showed symmetrical hyperinflation, suggesting bronchiolitis. No improvement occurred after 5 days therapy with bronchodilators and corticosteroid nebulization prompted flexible bronchoscopy, which revealed a round-shaped artificial pearl bead lodged at the lower end of the trachea, moving bidirectionally with respiration. The bead was successfully extracted using a ‘zero’ tip stone basket by flexible bronchoscopy. Post-removal, the child’s symptoms resolved completely, although she developed fever secondary to multidrug-resistant (MDR) Pseudomonas aeruginosa infection identified in bronchoalveolar lavage fluid, which responded to levofloxacin. This case illustrates how an atypical tracheal foreign body can mimic bronchiolitis, emphasizing the importance of early bronchoscopy in unexplained airway obstruction in children.DS (Child) H J 2024; 40(1): 60-63